Magnetic Nanoparticles for Application in Nanomedicine - Milan Timko; Peter Kopcansky; M. Koneracka; Vlasta Zavisova; N. Tomasovicova; A. Dzarova (Communications - Scientific letters of the University of Zilina, 2010)
This contribution will summarize the information about the ways of synthesizing biocompatible magnetic nanoparticles and complexes containing them and the possibility of their application in nanomedicine at magnetic drug targeting and thermal treatment of diseases by hyperthermia effect. Some procedures of the preparation of biocompatible magnetizable complexes as magnetic nanoparticles, magnetic fluids, some proteins and enzymes covalently bound to the freshly prepared magnetic nanoparticles in the presence of carbodiimide (bovine serum albumin, streptokinase, chymotrypsin, dispase, glucose oxidase), entrapment of magnetic particles into magnetoliposomes and encapsulation of clinically important drug as indomethacin and taxol together with magnetite nanoparticles in biodegradable polymer. We will summarize the results from the study of structural, magnetic and hyperthermic properties of bacterial magnetite nanoparticles i.e. magnetosomes prepared by biomineralization process of magnetotactic bacteria as a promising material for application in nanomedicine.